Você está na página 1de 22

FINITE DIFFERENCES

INTRODUCTION
Suppose x(0), x(1),...x(n) are sample input signals and y(0), y(1), ....y(n) output
signals as given in Fig.

Then we can form a table of values


x

xo x1 x2 x3 . . . xn-1 xn

yo y1 y2 y3 . . . xn-1 yn

If we subtract from each value of y (except y0) the proceeding value of y we get
y1 - y0, y2 - y1, .....yn - yn-1 .
These are called as first order forward differences of y and are denoted by y.
i. e y0 = y1 - y0, y1 = y2 - y1, .... yn-1 = yn - y n-1.
These are called first differences. From these we can form second order differences
2y0 = y1 - y0, 2y1 = y2 - y1, ... 2yn-1 = y2 - y1.
If x0, x1, x2, ,, xn are equally spaced then the input signals can be written as x0 + h,
x0 + 2h, ..... xn + h , so tha x1 - x0 = h = x2 - x1 etc.
We now define f(x)= f(x + h) - f(x).
Backward Differences:
The differences of the form y1 = y1 - y0, y2 = y2 - y1, .... yn = yn - y n-1.
LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 1

If x0, x1, x2, ,, xn are equally spaced then we define f(x)= f(x) - f(x - h). Second
order differences can be defined in a similar manner as forward differences.
Shifting Operator E:
The shifting operator or translation operator is defined as Eyn = y n+1.
So second and higher order differences are defined as Ey1 = y2, E2 y1 = y3.
Central Difference Operator :
The central difference is defined as = .

The Averaging difference operator :


The averaging differencing is defined as =

Relation Between Operators:

yn = yn+1 - y n = E yn - yn = (E - 1) yn

So

=1

Next = = = (1 )
= 1

So

Now we find the relation between central difference, averaging operator with
shifting operator.
= = = .

So

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 2

Similarly =

= /2

So

Relation Between Differential Operator and Other Operators:


The differential operator D is defined as = )(

By Taylor's theorem, ( + ) = ( )+
= 1 +

So

= ()

().

)(+

()
!

( )+ ..

+ f(x)

( = 1 + ) = . So = log ()

Since

1
= +
2

= ( )

= ( )

= sin h(hD)
= ()

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 3

PROBLEMS
1)With usual notations, prove that
We know that =1- , =E-1

LHS =

=
=

=E

= E

= RHS

2)With usual notations prove that = + 1 +

We know that = 1, =

LHS = E-1

RHS = + 1 + 4

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 4

+
+

=E-1
=LHS

3) Establish the result =

()

with usual notations

W.K.T
=E-1
R.H.S =

= ( + ) = = L.H.S

4) Prove with usual notations that1+

= (1 + )

R.H.S

(1 + ) =( + )
= +

( ) ( )

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 5

= +

=
=
=
=
=

( )

+ =1 + /

5) Prove that hD= log(1+) = sin ()

Solution: We know that : 1+ = E ; E =


LHS:log (1+) = log E

So log (1+) = hD

RHS: =





( )

So = sinh (hD)

Hence sin () = hD

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 6

Question 6) = 1 +

= 1 +
=

()
[
]

( )

/ /

=
=

[ / / ]
/

/ /

= /

7) Show that (1+)(1-) = 1 with usual notation.


We Know that = E -1

=1-E -1

LHS =(1+E-1)(1-1+E -1)


= (E)(E -1) = 1 = RHS

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 7

SOLUTION OF FINITE DIFFERENCE EQUATION


INTRODUCTION
An equation which expresses a relation between the independent variable, the
dependent variable and the successive differences of the dependent variable is
called a difference equation.
Example: + 5 + 6 =

4 + 5 + 6 = sin + 2

Using the relation, = 1, = ( 1) ,

and so = ( 1) =

= ( 1) = 2 +

Hence : + 5 + 6 = can be written as


2 + + 5( ) + 6 = 2

i.e + 3 + = 2 or ( + 3 + 2) = 2

Linear Difference of Higher Order Difference Equation


A general linear difference equation of higher order is of the form
a0yx+n + a1yx+n-1 + .. + anyn = (x)

(1)

or (a0En + a1En-1+.+ an-1E + an)yx = (x)

(2)

i.e f(E)yx = (x)

(3)

The solution of (3) is the sum of Complementary Function and Particular Integral.
i.e. yx = Complementary Function + Particular Integral

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 8

Method of finding Complementary Functions


Consider the equation f(E) = 0

(1)

Form auxiliary equation by replacing E by a in eqn.(1), we get f(a) = 0

(2)

Find the roots of eqn.(2). Let it be a1, a2,..., an


Now three cases arise.
CASE 1. Let all the roots of eqn. (2) be real and distinct.
Then . = + + +
(3)

CASE 2. Let a1 = a2 = a, and the a=other roots a3,a4, ... , an are real and distinct.
Then . ( = + ) + + +

(4)

Then . = ( cos + sin )+ + + ,

(5)

CASE 3. Let a1 = + i, a2 = - i, a3,a4, ... , an are real and distinct.

where = + , = .

Methods of Finding Particular Integral


The particular integral is defined by . =
CASE 1. Let ( = ) .

Then . =

()
()

, () 0.

If f(a)=0, then . =

()

()
!

()
()

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

(7)

Page 9

where ( ) = ( 1)( 2. . . ( 1).


CASE 2. Let ( = )sin .
Then . =


()

()

()

CASE 3. . Let ( = )sin .

Then . =


()

()

()

()

, = , =

()

(8)

, = , =

(9)

CASE 4. Let ( )
Then . =

()

()

= [1 ()] ()

(10)

Expand [1 ()] as a series of ascending powers of and operate on (x)

1) Solve : 5 + 6 = 0
Solution:

[ 5 + 6] = 0

The auxillary equation is.


( 5 + 6) = 0

( 1)( 2) = 0
m= 3,2
CF = 3 + 2

= 3 + 2

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 10

2 : + 7 + 8 = 0
Solution:

Given equation can be written as [ + 7 + 8] = 0


The auxillary equation is
( + 7 + 8) = 0

The roots are : m =


CF = _ 

 
,







&

+ _ 





&

3) Find particular integral of &Y 12& + 16& = 2& + 4&


Solution:
s
! !

kl =

s

=  
s
?

=
..ie

kl =

kl =

& 
!

. 2& 

&& 


s

. 2& 

?s

! !

=
kl

?s

? ?

= kl + kl =

&& 


?s
Y
?s

. 2&  + Y

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 11

PROBLEMS PART B
1) Solve u x + 2u x = cos x
u x + 2 u x = cos x
= E 1
n = ( E 1) n
u x = ( E 1)u x = Eu x u x
2 = ( E 1) 2 u x = ( E 2 2 E + 1) u x = E 2 u x 2 Eu x + u x
u x +1 u x + u x + 2 2u x +1 + u x = cos x
u x + 2 u x +1 = cos x
E2

E
= cos x
ux

( E 2 E )u x = 0 a 2 a = 0 a (a 1) = 0 a = 0,1
CF = C1 (1) x
PI =

( x)
F (E)

cos x
E2 E

= real part of
= real part of

= real part of

= real part of

=real part of

, Replace E by a=

( )( )

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 12

=real part of
=

() ()
( )

()

The Solution is = (1) +

()
( )

2) Solve yx+27yx+18yx=x(x2)2x
Solution: (E27E8)yx=(x2-x)2x

Auxiliary equation: m27m8=0


(m8)(m+1)=0

m=8, m=1
C.F=C18X+C2(1)x
P.I:
P.I=

()

P.I=2x

()

()

=2

= 2

(REPLACE E=aE=2E)

()

= 2
= 2

2x

()

() ()
()

( )
()

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 13

= 2
=
=
=
=
=

()

P.I=

1 (

1 +

1 +

( )

()

( )

( )

( 1)

()

= . + .

( )

= 8 + (1)

+ .

3) Solve (E - 6E + 8) =3n + 6 5(3 )


[(E-4) (E-2)] =3n +6 - 5(3 )

A.E: m2 - 6m + 8 = 0

The roots are m=4, m=2

P.I = ()()[3n + 6 - 5(3 )]


= 3()()(n+2) - 3

=
=

()()

(5)

( )

(n+2) - ()()
()()

()()

(n+2) + (5) (3 )

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 14

= 1 +

(n+2) + 5(3 )

= 1 +

= [1-

= [1 +

(n+2) + 5(3 )

] (n+2) + 5(3 )

] (n+2) + 5(3 )

= n + 2 + [(2n+1)] +

= n + n + +

[2] + 5(3 )

+ 5(13 )

=n + n + 5(13 ) +

(n + 2) + 5(3 )

=n + n + 5(13 ) +

4) Solve 2 + 5 = 2. 3 4. 7
SOLUTION:

A.E: 2 + 5 = 0
ROOTS ARE :

1+2i,1-2i

C.F = ( (. ) + (. ))
TO FIND P.I:

P.I=P.I 1+P.I 2
()

P.I 1=
=

()

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 15

Put E=aE,
=

.2

. ()

P.I 2=

=
=

.4

{y(x)}=C.F+P.I 1+P.I 2
=1 (1 cos(63.43) + C2 sin(63.43))+

5) SOLVE:

( + 2 + = . 2 )
( + 2 + 1) = . 2

The auxillary equation is obtained by replacing E=a


+ 2 + 1 = 0

( + 1) ( + 1) = 0
a =-1,-1

To find P.I

C.F =( + ) (1)

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 16

P.I =

=
=
=
=
=

() ()

() ()

( )

= [1 +

P.I = [9 12]

= . + .

= ( + ) (1) +

[9 12]

6) Solve 2 -7 +3 =cos 2

Solution: Rewriting the given equation as: 2 -7E+3=0


Auxiliary equation: 2 -7m+3=0
( 3)(2 1)=0

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 17

m=3,12

complementary equation()= (3 )+ 12

particular integral(PI)=

= R.P of

Replace E by

=(


)

=R.P of
=
=

. . .

. () ()

( )
() ()

Solution=cf+PI= (3 )+ (12) +
General

() ()

() ()

7) 8 + 12 = sin
Solution:

( 8 + 12) = sin

8 + 12 = 0

( 2)( 6) = 0
= 2,6

. = 2 + 6
LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 18

. =

=
=

)( ,

sin
8 + 12


()()

()()

()()

= (1)

( 2)( 6)
( 2)( 6)
=

= ()()

= + 1

= (())(())

= ()()

=
=

12 1 + 1 +
2
6

+
+ ()
=
1
1

12
2
6

+
+
+
+
=
1 +
+
1 +
+
()
12
2
2
6
6
LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 19

+ + 2
+ + 2 ()
1 +
+
1 +
+

12
2
4
6
36

+ + 2
1 +
+
(36 + 6 + 6 + + 2 )()
12 36
2
4

+ + 2
1 +
+
(36 + 6 + 6 + + 2 )
2
432
4

[(4 + 2 + 2 + + 2 )(36 + 6 + 6 + + 2 )]
432 4

[(4 + 2 + )(36 + 6 + 6 + + 2 ) + (2 + 2 )(36 + 6 + )]


1728

[ ( + 4) + (8 + 18) + (16 + 98) + (96 + 96)]


=
1728
=

= ,

1
( + 4) + (8 + 18) + (16 + 98)
1728
+ (96 + 96) + 144]


( 2)( 6)

1
( + 4) + (8 + 18) + (16 + 98)
1728
+ (96 + 96) + 144 ]
1,

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 20

1
() () ( + 4) + () () (8 + 18)
1728 2
+ () () (16 + 98)
+ () () (96 + 96) + 144(
=

[sin( + 4)( + 4) + sin( + 3)(8 + 18)


1728
+ sin( + 2)(16 + 98) + sin( + 1)(96 + 96) + 144 sin ]

[sin( + 4)( + 4) + sin( + 3)(8 + 18)


1728
+ sin( + 2)(16 + 98) + sin( + 1)(96 + 96) + 144 sin ]

= . + .

= 2 + 6

[sin( + 4)( + 4) + sin( + 3)(8 + 18)


1728
+ sin( + 2)(16 + 98) + sin( + 1)(96 + 96) + 144 sin ]

Solve

( + 2) + ( + 1) 56() = 2 ( 3)

Take E operator on LHS

( + 56)() = 2 ( 3)
() =

2 ( 3)
+ 56

Replace E by E-2 so as to remove the exponential from the E operator.


3
() = 2
( 2) + 2 56

Replace E by 1+ . And n squared by factorial polynomials.

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 21

() = 2

() + ()
56

() + ()
() = 2 (1/56)

1+( )
56 56

1

() = 2 1 +
56
56 56

(() + () )

1


() = 2 (1 + )(() + () )
56
56 56
56 56

() = 2

(2 + 1) 2 2
1
(() + ()
+
56
56
56

() = 2

1
2 + 1
( 1) +

56
56

() = 2

1
(56 (2 + 1))
56

LECTURE NOTES FINITE DIFFERENCE EQUATION BY Dr. V.GNANARAJ

Page 22

Você também pode gostar